2020
DOI: 10.1016/j.marpol.2020.103953
|View full text |Cite
|
Sign up to set email alerts
|

The global costs and benefits of expanding Marine Protected Areas

Abstract: General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. • Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 62 publications
2
39
0
3
Order By: Relevance
“…From the economic viewpoint, a recent analysis by Brander et al. (2020) has shown that the global benefits of expanding MPAs exceed their costs.…”
Section: Discussionmentioning
confidence: 99%
“…From the economic viewpoint, a recent analysis by Brander et al. (2020) has shown that the global benefits of expanding MPAs exceed their costs.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is progressively and strongly dependent on the capacity to go beyond the classical bedrock and mobilize, articulate and provide diverse and innovative financial sources and mechanisms. It also includes the coordination of complementary elements, components and projects, and the involvement of diverse stakeholders (Brander et al, ; Bos et al, ; Watson et al, ). There are several possibilities for alternative and additional sources of funding for federal marine protected areas.…”
Section: Building a New Strategymentioning
confidence: 99%
“…Establishing and managing protected areas is not inexpensive, and this is particularly true for marine protected areas. A cost of US $45–47 billion has been estimated for achieving 10% global ocean protection between 2015 and 2050 (Brander et al, ). In several cases, countries and national agencies might not be able to dedicate enough attention, strengthen integration among governmental and private sectors and provide adequate enough staff and budget (Bos, Pressey, & Stoeckl, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations